Teachers' perceptions of the barriers to effective teaching in Qatar's government schools - Reem Khalid Abu‐Shawish (22225507) (2024)
This study sought to identify the barriers to effective teaching from the perspective of teachers in Qatar's government schools. This study used survey questionnaire data from the Qatar Education Study 2018, a nationally representative sample of 424 school teachers, to determine what they consider the top barriers facing them as they work to provide effective instruction. The current study seeks to understand how the five different systems of the ecological systems theory influence effective teaching in the context of Qatar. Based on Stata 16 data analyses, percentages and mean ratings were used to identify salient barriers to effective teaching. Results indicated that student‐related barriers, such as motivation and differing student abilities, and school‐related barriers, including teachers' workload, influence effective instruction. A discussion of pertinent results is offered, and relevant recommendations for policy‐making intervention and calls for future study and research are provided. Other Information Published in: European Journal of Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/ejed.12711